Editorial Special Section on Invited Papers in 2022 on Emerging Topics in the Power and Energy Society - Fangxing Fran Li (IEEE Open Access Journal of Power and Energy, 2022)
The 2020 and 2021 Special Sections on Invited Papers on Emerging Topics in the Power and Energy Society (PES) proved to be of broad interest to diverse readers in the PES community, and the publication of this new section marks the third year in a row for the special invited section. After a rigorous peer-review process, a total of 13 articles were accepted for publication in the 2022 invited section of the IEEE Open Access Journal of Power and Energy (OAJPE).